Lipid layer thickness and tear meniscus height measurements for the differential diagnosis of evaporative dry eye subtypes - Xuan Sang; Yan Li; Liu Yang; Jia-Hui Liu; Xiao-Ran Wang; Chao-Yang Li; Ying Liu; Chen-Jie Wang; Xiong-Jun He; Shou-Bi Wang; Zhi-Chong Wang (International Journal of Ophthalmology, 2018)
AIM: To explore a new diagnostic index for differentiating the evaporative dry eye (EDE) subtypes by analysis of their respective clinical characteristics. METHODS: A cross-sectional study of 139 patients (139 eyes) with EDE who were enrolled and classified as obstructive meibomian gland dysfunction (MGD) (n=81) and non-obstructive MGD (n=58) EDE. All patients completed a Standard Patient Evaluation of Eye Dryness (SPEED) questionnaire and were evaluated for average lipid layer thickness (LLT), tear meniscus height measurements (TMH), tear break-up time (TBUT), ocular surface staining score, Schirmer I test (SIT), lid margin abnormalities, and meibomian gland function and morphology. RESULTS: Age, average LLT, TMH, scores of lid margin abnormalities, meibum quality, meibomian gland loss (MGL) (all P≤0.001), and TBUT (P=0.03) were all significantly different between obstructive MGD EDE patients and non-obstructive MGD EDE patients. Average LLT in obstructive MGD EDE was correlated with meibomian expressibility (r= -0.541, P≤0.001), lid margin abnormalities were marginally not significant (r=0.197, P=0.077), and TMH was correlated with MGL (total MGL: r=0.552, P≤0.001; upper MGL: r=0.438, P≤0.001; lower MGL: r=0.407, P≤0.001). Average LLT in non-obstructive MGD EDE, was correlated with meibomian expressibility and Oxford staining (r=-0.396, P=0.002; r=-0.461, P≤0.001). The efficiency of combining average LLT and TMH was optimal, with a sensitivity of 80.2% and a specificity of 74.1%. Obstructive MGD EDE patients had an average LLT≥69 nm and TMH≥0.25 mm, while non-obstructive MGD EDE patients had an average LLT<69 nm and TMH<0.25 mm. CONCLUSION: Obstructive MGD EDE and non-obstructive MGD EDE have significantly different clinical characteristics. Combining average LLT and TMH measurements enhanced their reliability for differentiating these two subtypes and provided guidance for offering more precise treatments for EDE subtypes.